LEGAL PROTECTION FOR DEBTORS IN SHARIA ECONOMIC CASES SKMHT DECISION NUMBER 723/PDT.G/PA Gtlo - Yopa Emalia Fajarini; Henry Aspan; Dahlan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This journal discusses the legal issues related to the disbursement of financing facilities amounting to Rp. 80,000,000,- by DEFENDANT I without any valid Mortgage Rights binding on SHM No. 34/Buladu, which resulted in the disbursement being considered invalid. Decision Number 723/PDT.G/2021/PA.Gtlo confirms that the deeds made do not meet the formal requirements and must be declared null and void by law. This study also highlights legal protection for debtors in the context of sharia economics, with a focus on fiduciary guarantees regulated in Law No. 42 of 1999. The case discussed involves the confiscation of fiduciary guarantee objects due to the debtor's default, as well as the importance of SKMHT (Power of Attorney to Charge Mortgage Rights) as a legal instrument to secure the creditor's position. This study uses normative legal methods and identifies the factors causing the debtor's default, as well as the correct procedures in issuing APHT (Deed of Granting Mortgage Rights). The results of the study indicate that there is abuse of conditions in the agreement and breach of promise by the debtor, and emphasize the importance of understanding the rights and obligations of debtors and creditors in debt agreements.